A rare case of plasma cell osteomyelitis with atypical presentation - Meghalamane, Mallikarjuna Reddy Rowdur; Kumar, Alla Vasanth; Avinash, Gandham Satya; Surendra, Yellapu (International Journal of Research in Orthopaedics, 2019)
Plasma cell osteomyelitis is an uncommon type of localized chronic osteomyelitis which is characterized by the absence of typical clinical features of infection. It usually affects the metaphysis of long bones and presents as dense thickening of bone without sequestrum formation. We present an atypical case of plasma cell osteomyelitis with a lesion in the diaphysis of long bone and sequestrum formation. A 23 year old male patient came to our OPD with complaint of pain in mid-thigh radiating to the left knee since 2 months. X-ray showed radiolucencies in the medulla of middle third of shaft of femur along with a linear sequestrum suggestive of chronic osteomyelitis. An open biopsy was performed and surgical curettage was done. Histopathological examination was consistent with plasma cell osteomyelitis. Chronic plasma cell osteomyelitis is a rare condition with nonspecific findings and an unclear cause. Histopathology is the definitive tool for obtaining a diagnosis. Knowledge of this condition and proper management can give a better outcome, at the same time avoiding unnecessary investigations and procedures.